Modelling and analysis of the mechanical properties of agave sisalana variegata fibre / vinyl ester composites using box-behnken design of response surface methodology - Athijayamani, Ayyanar (Strojniški vestnik, 2016)
In this paper, the Box-Behnken (BB) experimental design of response surface methodology (RSM) was utilized to study the effect of process parameters on the mechanical properties of agave sisalana variegata (ASV) fibre-reinforced vinyl ester (FRVE) composites. The fibre length, fibre content, and fibre diameter were used as process parameters to develop a model using the BB experimental design. Experimental tests were carried out based on the BB design. The experimental tensile and flexural strength values were fitted with the predicted strength values by a second-order polynomial equation via a multiple regression analysis. The results show that the tensile and flexural strength can be predicted by the developed models with more than 98.54 % of the variation in the tensile strength and 99.24 % of the variation in the flexural strength. The level 3 of fibre length (13 mm), level 2 of fibre content (35.19 wt %), and level 1 of fibre diameter (0.24 mm) were selected as the optimal levels of fabrication process parameters using the response surface graph and models. Finally, it was proved that the BB design of response surface methodology could efficiently be applied to the modelling and optimization of the mechanical properties of natural fibre polymer composites.
Keywords: kompoziti; metodologija odzivne površine; natezna trdnost; upogibna trdnost; vlakna Agave sisalana variegata; zasnova Box Behnken